Relation among absorbance shifts, mineralization morphology, and electronic conductivity of π-peptide aggregates with different amino acid residues. Issue 8 (5th April 2023) - Lee, Taein; Panda, Sayak Subhra; Hall, Grant E. K.; Song, Yunjia; Tovar, John D.; Katz, Howard E.
Abstract : Three conceivably unrelated observations on peptide assemblies; absorbances, morphologies, and conductivities are interrelated. An alanine methyl group was sufficient to alter all three observations, a steric effect from a small perturbation. Abstract : Previously, the structures of self-assembled π-peptide aggregates, upon shifting from basic to acidic medium, have been shown computationally to vary greatly when the closest amino acid to the π-cores are varied between glycine and alanine. The absorbance spectra of π-peptide aggregates with different self-assembled structures showed different spectral shifts between acidic and basic medium. The relation of the absorbance shifts to various material properties of solid-state thin films made from the π-peptides by exposing basic medium to acid vapor were investigated for two types of π-cores: α-quaterthiophene (4T) and perylene diimide (PDI). π-Peptide nanostructure-templated mineralization of KCl was used as an indicator of structural morphology, which was further connected to electronic properties of the thin films. Thin films of π-peptides with 4T cores showed higher conductivity for samples with conspicuous KCl XRD peaks, which corresponded to samples with greater absorbance spectra shift from basic to acidic medium. Thin films of π-peptides with PDI cores that have glycine amino acids closest to the π-cores were previously shown by computational molecular dynamics simulation to exhibit co-facial stacking, while those with alanine amino acids closest to the π-cores were shown to exhibit rotationally shifted stacking. Self-assembled thin films of co-facially stacked π-peptides exhibited templated mineralization of dendritic KCl structures and good surface adhesion between thin film and the underlying substrate. On the other hand, those of rotationally shifted stacking π-peptides exhibited sporadic spots of bulk mineralized KCl and extreme brittleness of thin film due to poor adhesion with the underlying substrate. The observed brittleness in all rotationally shifted stacking π-peptide thin films made it impossible to accurately measure electrical properties, while co-facially stacked π-peptide thin films showed notable electrical conductivity.